Perfil do suspeito e racismo institucional : uma análise da ação policial em Uberlândia, Minas Gerais - Jesus, Andreia Sousa de (2017)
The present study analyzes the social barriers established institutionally by the public administration and that condition the stigmatization of the black population. Remains of the enslavement process in Brazil endure today in a complex and emblematic way. Race remains in the collective imaginary constructed from phenotypic differences that configured as representations of subjects' subjectivity, however, acting in an objective way in everyday life. Housing programs function as an artifice of allocating the black population in the peripheries, and it considered that this is an institutionally racist practice. The state's repression of this population does not arise in police violence, but in tendentious actions that determine spaces for certain individuals. Institutionally organized police violence is yet another way to prevent the social, political, economic and intellectual rise of the black population.